Molecular and clinical analyses of Helicobacter pylori colonization in inflamed dental pulp - Ryota Nomura; Yuko Ogaya; Saaya Matayoshi; Yumiko Morita; Kazuhiko Nakano (BMC, 2018)
Abstract Background Recently, dental pulp has been considered a possible source of infection of Helicobacter pylori (H. pylori) in children. We previously developed a novel PCR system for H. pylori detection with high specificity and sensitivity using primer sets constructed based on the complete genome information for 48 H. pylori strains. This PCR system showed high sensitivity with a detection limit of 1-10 cells when serial dilutions of H. pylori genomic DNA were used as templates. However, the detection limit was lower (102-103 cells) when H. pylori bacterial DNA was detected from inflamed pulp specimens. Thus, we further refined the system using a nested PCR method, which was much more sensitive than the previous single PCR method. In addition, we examined the distribution and virulence of H. pylori in inflamed pulp tissue. Methods Nested PCR system was constructed using primer sets designed from the complete genome information of 48 H. pylori strains. The detection limit of the nested PCR system was 1-10 cells using both H. pylori genomic DNA and bacterial DNA isolated from inflamed pulp specimens. Next, distribution of H. pylori was examined using 131 inflamed pulp specimens with the nested PCR system. In addition, association between the detection of H. pylori and clinical information regarding endodontic-infected teeth were investigated. Furthermore, adhesion property of H. pylori strains to human dental fibroblast cells was examined. Results H. pylori was present in 38.9% of inflamed pulp specimens using the nested PCR system. H. pylori was shown to be predominantly detected in primary teeth rather than permanent teeth. In addition, samplings of the inflamed pulp were performed twice from the same teeth at 1- or 2-week intervals, which revealed that H. pylori was detected in most specimens in both samplings. Furthermore, H. pylori strains showed adhesion property to human dental fibroblast cells. Conclusion Our results suggest that H. pylori colonizes inflamed pulp in approximately 40% of all cases through adhesion to human dental fibroblast cells.